PENINGKATAN KETERAMPILAN BERPIKIR KREATIF DAN HASIL BELAJAR BIOLOGI SISWA MENGGUNAKAN MODEL PEMBELAJARAN GGE (Group To Group Exchange) DENGAN Sequence Chains (PADA BAHASAN EKOSISTEM KELAS X MIPA 4 SMAN 1 GAMBIRAN BANYUWANGI) - Hana Himatul ‘Aliyah; Joko Waluyo; Kamalia Fikri (Saintifika, 2017)
Abstract: The research is a classroom action researched aiming to improved creative thinking skilled and biology learning result by implemented GGE (Group to Group Exchange) learning model with Sequence Chains on students of class X MIPA 4 SMAN 1 Gambiran Banyuwangi academic year 2017/2018 which is done two cycles. Stages cycles includes: planning, action, observation, and reflection. The result of the research of creative thinking skill on pre-cycle is 32,02 increased 43,82 to be 75,85. In learning result, pre cycle cognitive learning comprehensiveness is 43,75% increased 37,5% to be 81,75%, while for effective achievement in the pre-cycle is 36,71 increased 41,58 to be 78,32. Based on the above explanation, it can be concluded that the implementation of GGE (Group to Group Exchange) with Sequence Chains can improve creative thinking skill and learning result of students class X MIPA 4 SMAN 1 Gambiran Banyuwangi academic year 2017/2018. Keywords: GGE (Group to Group Exchange), Sequence Chains, Creative Thinking, Learning Result.